Long‐Term Simulation of Snow Cover and Its Potential Impacts on Seasonal Frost Dynamics in Croplands Across Southern Canada. Issue 8 (22nd August 2022) - Li, Ziwei; Qi, Zhiming; Smith, Ward; Pattey, Elizabeth; Qian, Budong
Abstract: In northern climates, accurate simulation of thermal and hydrological budgets for farmlands overwinter is crucial for both an accurate prediction of spring flooding and the successful management of nutrient losses. As snow cover influences soil freezing dynamics, it has been hypothesized that reduced snow cover due to warmer winters might intensify soil freezing. The present study was designed to test this hypothesis. Drawing upon observed snow depth and soil temperature data collected from six research farms across Southern Canada over various time spans from 1989 to 2020, the root zone water quality model, integrated with the simultaneous heat and water model (RZ‐SHAW), was calibrated and validated. The potential influence of warmer winter on shifts in soil frost dynamics was evaluated by estimating soil freezing dynamics for each farmland site under various air temperature scenarios using the RZ‐SHAW model. Soil frozen depth in the eastern Canada sites increased with increasing air temperature in some years but decreased under the highest air temperature increases of 3.5°C. The monthly relationship between snow depth and soil frozen depth was determined through partial correlation analysis. Snow was most effective in alleviating soil freezing in the months of January and February, a period when snow cover depth was least affected by warming air temperatures. This study suggests that the hypothesis of increasing soil frozen depth under global warming‐induced snow cover reduction holds true in conditions where soil energy lost through reduced snow cover outweighed the soil energy gained through warmer air temperature. Plain Language Summary: Snow cover is a critical surface condition affecting the freezing dynamics of the soil during winter. However, snow depth tends to decrease across the globe as climate change continues. Previous research has hypothesized that the global warming‐induced snow cover reduction would lead to intensified soil freezing through in situ snow manipulation experiments. In this study, we use a physical model to simulate the soil winter conditions for six croplands in Canada to understand the change of soil freezing dynamics under rising air‐temperature induced snow depth reduction and the monthly relationship between snow depth and soil frozen depth across the winter. We suggest that the influence of warmer winter‐induced snow cover reduction on the soil freezing dynamics is not linear but a function of the soil net energy change under warmer air temperature and reduced snow insulation. This information could be useful for agricultural management, such as adjusting the pipe depth for irrigation and drainage pipes, the timing to close and open the control drainage gate, and the tillage date and the seedling date for cold regions under climate change. Key Points: Root zone‐simultaneous heat and water model performs better in simulating soil freezing in croplands located in Southeastern Canada compared to Southwestern Canada Deeper soil frozen depth may occur if the energy lost though the reduced snow insulation outweighs the energy gained from the warmer winter Under warmer temperature scenarios, deeper soil frozen depth was simulated in a few years only for croplands located in Southeastern Canada